Territorial revisions to increase cohesion policy funding from the EU: the case of the new member states - Zdražil, Pavel; Kraftová, Ivana (Routledge, 2023)
This paper argues that some EU member states have been smart, or even dishonest. Splitting off capital cities from existing NUTS2 regions has given them an advantage in the Cohesion Policy funds allocation scheme but worsened the position of others. To explain the reasons and implications, we review the issue of delimiting the NUTS2 regions and the related allocation of financial resources. We evaluate how modifications of NUTS2 regions, carried out by Hungary, Poland, and Lithuania, impacted the allocation of financial resources for the 2021-2027 programming period. The analysis shows the shift of billions of euros towards these countries. We also argue that this experience is and could also be an inspiration for other countries.
Revize vymezení regionů s cílem zvýšit financování politiky soudržnosti ze strany EU: případ nových členských států
Keywords: Cohesion Policy; European integration; allocation mechanism; NUTS2 regions; rivalry; Politika soudržnosti; evropská integrace; alokační mechanismus; regiony NUTS2; rivalita